Retinal hemodynamic oxygen reactivity assessed by perfusion velocity, blood oximetry and vessel diameter measurements. (1st October 2014) - Klefter, Oliver Niels; Lauritsen, Anne Øberg; Larsen, Michael
Abstract Purpose To test the oxygen reactivity of a fundus photographic method of measuring macular perfusion velocity and to integrate macular perfusion velocities with measurements of retinal vessel diameters and blood oxygen saturation. Methods Sixteen eyes in 16 healthy volunteers were studied at two examination sessions using motion‐contrast velocimetry and retinal oximetry with vessel diameter corrections. To test oxygen reactivity, participants were examined during normoxia, after 15 min of hyperoxia and finally after 45 min of normoxia. Repeatability was assessed by intraclass correlation coefficients (ICC) and limits of agreement. Results Fifteen minutes of hyperoxia was accompanied by mean reductions in arterial and venous perfusion velocities of 14% and 16%, respectively (p = 0.0080; p = 0.0019), constriction of major arteries and veins by 5.5% and 8.2%, respectively (p < 0.0001), increased retinal arterial oxygen saturation from 95.1 ± 5.0% to 96.6 ± 6.4% (p = 0.038) and increased retinal venous oxygen saturation from 62.9 ± 6.7% to 70.3 ± 7.8% (p = 0.0010). Parameters returned to baseline levels after subsequent normoxia. Saturation and vessel diameter ICCs were 0.88–0.98 (range). For perfusion velocities, short‐term ICCs were 0.79–0.82 and long‐term ICCs were 0.06–0.11. Intersession increases in blood glucose were associated with reductions in perfusion velocities (arterial p = 0.0067; venous p = 0.018). Conclusion Oxygen reactivity testing supported that motion‐contrast velocimetry is a valid method for assessing macular perfusion. Results were consistent with previous observations of hyperoxic blood flow reduction using blue field entoptic and laser Doppler velocimetry. Retinal perfusion seemed to be regulated around individual set points according to blood glucose levels. Multimodal measurements may provide comprehensive information about retinal metabolism.